Respuesta :
Answer:
[tex]f(x) = -\frac{x^{3}}{2} - \frac{x^{2}}{3} + \frac{65x}{6} - 6[/tex]
Step-by-step explanation:
We use a system of equations to solve this question.
f(0) = −6
This means that when [tex]x = 0, f(x) = -6[/tex]. So
[tex]f(x) = ax^{3} + bx^{2} + cx + d[/tex]
[tex]-6 = a*0^{3} + b*0^{2} + c*0 + d[/tex]
[tex]d = -6[/tex]
So
[tex]f(x) = ax^{3} + bx^{2} + cx - 6[/tex]
f(1) = 4
This means that when [tex]x = 1, f(x) = 4[/tex]
So
[tex]f(x) = ax^{3} + bx^{2} + cx - 6[/tex]
[tex]4 = a*1^{3} + b*1^{2} + c*1 - 6[/tex]
[tex]a + b + c = 10[/tex]
f(3) = 10
This means that when [tex]x = 3, f(x) = 10[/tex]
So
[tex]f(x) = ax^{3} + bx^{2} + cx - 6[/tex]
[tex]10 = a*3^{3} + b*3^{2} + c*3 - 6[/tex]
[tex]27a + 9b + 3c = 16[/tex]
f(4) = 0
This means that when [tex]x = 4, f(x) = 0[/tex]
So
[tex]f(x) = ax^{3} + bx^{2} + cx - 6[/tex]
[tex]0 = a*4^{3} + b*4^{2} + c*4 - 6[/tex]
[tex]64a + 16b + 4c = 6[/tex]
So we have to solve the following system of equations:
a + b + c = 10
27a + 9b + 3c = 16
64a + 16b + 4c = 6
From the first equation:
a = 10 - b - c
Replacing on the second, and on the third:
[tex]27(10 - b - c) + 9b + 3c = 16[/tex]
[tex]270 - 27b - 27c + 9b + 3c = 16[/tex]
[tex]18b + 24c = 254[/tex]
And
[tex]64(10 - b - c) + 16b + 4c = 6[/tex]
[tex]640 - 64b - 64c + 16b + 4c = 6[/tex]
[tex]48b + 60c = 634[/tex]
So
18b + 24c = 254
48b + 60c = 634
Multiplying the first one by 5, and the second one by -2, to eliminate c
90b + 120c = 1270
-96b - 120c = 1268
[tex]-6b = 2[/tex]
[tex]6b = -2[/tex]
[tex]b = -\frac{1}{3}[/tex]
Then
[tex]18b + 24c = 254[/tex]
[tex]24c = 254 - 18b[/tex]
[tex]24c = 254 - 18\frac{-1}{3}[/tex]
[tex]24c = 260[/tex]
[tex]c = \frac{65}{6}[/tex]
And
[tex]a = 10 - b - c = 10 -(-\frac{1}{3}) - \frac{65}{6} = -\frac{1}{2}[/tex]
So
[tex]f(x) = -\frac{x^{3}}{2} - \frac{x^{2}}{3} + \frac{65x}{6} - 6[/tex]